Kesaksian Rukyatul Hilal dalam Tinjauan Astronomi dan Hukum Acara Peradilan Agama Indonesia - Mubarok, Muhammad Zaki; Azkarrula, Youla Afifah (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2022)
The condition of the pluralistic Indonesian society and various mass organizations raises various views regarding the determination of the beginning of the lunar month. This view is caused by differences in understanding and interpretation of verses and hadiths relating to the beginning of the lunar month. In Indonesia there was a case where when the new moon was below the criteria there was someone who testified to see the new moon and dared to take an oath. In essence, this is contrary to the view of astronomy and civil law in Indonesia. This research is included in the literature research with a qualitative approach. The results showed that astronomically and the procedural law of the religious courts, a person who testifies to seeing the new moon will be validated in astronomy through field data obtained as well as by the procedural law of the religious courts by fulfilling the requirements and criteria that apply in Indonesia, weather conditions that allow it to be seen. hilal, and in accordance with the Decree of the Supreme Court of the Republic of Indonesia Number KMA/095/X/2006.